(untitled) (International Journal of Engineering and Computer Science, 2025)
Quantum computing is revolutionizing computational paradigms by leveraging principles of quantum mechanics, such as superposition, entanglement, and interference, to solve complex problems that are intractable for classical computers. This paper explores the advancements in quantum algorithms and their transformative applications in two critical domains: cryptography and machine learning. Significant progress has been made in the development of quantum algorithms such as Shor’s algorithm, which threatens classical encryption methods like RSA, and Grover’s algorithm, which provides a quadratic speedup for search problems. These breakthroughs have highlighted both the vulnerabilities of classical cryptographic systems and the need for post-quantum cryptography to ensure data security in the quantum era. Simultaneously, quantum machine learning (QML) is emerging as a powerful tool, promising exponential improvements in data processing and model optimization through algorithms like Quantum Support Vector Machines (QSVMs) and Quantum Neural Networks (QNNs). Despite these advancements, the field faces significant challenges, including hardware scalability, noise, error correction, and the integration of quantum and classical systems. This paper provides a comprehensive review of the current state of quantum algorithms, their applications in cryptography and machine learning, and the associated challenges. It also outlines the future directions and interdisciplinary research opportunities required to address these limitations and harness the full potential of quantum computing in practical, real-world applications.